2017
DOI: 10.14814/phy2.13292
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between cerebral arterial inflow and venous outflow during dynamic supine exercise

Abstract: The regulation of cerebral venous outflow during exercise has not been studied systematically. To identify relations between cerebral arterial inflow and venous outflow, we assessed the blood flow (BF) of the cerebral arteries (internal carotid artery: ICA and vertebral artery: VA) and veins (internal jugular vein: IJV and vertebral vein: VV) during dynamic exercise using ultrasonography. Nine subjects performed a cycling exercise in supine position at a light and moderate workload. Similar to the ICA BF, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…This leads to blood pooling in the jugular venous system, which may compensate for the cerebral hyperperfusion. Our previous studies (29,36) also demonstrated in humans that there is coupling between regulations of arterial inflow and venous outflow in both anterior and posterior cerebral circulation. As with ECA vasculature, similarly, venous blood distribution may prevent a decrease in ICA blood flow in the present study when increasing hydrostatic pressure, but further investigations are needed to identify this important aspect of cerebral blood flow regulation.…”
Section: Discussionmentioning
confidence: 82%
“…This leads to blood pooling in the jugular venous system, which may compensate for the cerebral hyperperfusion. Our previous studies (29,36) also demonstrated in humans that there is coupling between regulations of arterial inflow and venous outflow in both anterior and posterior cerebral circulation. As with ECA vasculature, similarly, venous blood distribution may prevent a decrease in ICA blood flow in the present study when increasing hydrostatic pressure, but further investigations are needed to identify this important aspect of cerebral blood flow regulation.…”
Section: Discussionmentioning
confidence: 82%
“…The VV only compensates only for up to 50% of the reduction in IJV blood flow because of its smaller caliber, but other veins, such as the epidural veins, also drain the brain and help to regulate CBF during orthostatic stress. The orthostatic stress-induced alteration in venous drainage distribution affects arterial CBF regulation, especially in the posterior cerebral circulation (Ogoh et al, 2016(Ogoh et al, , 2020Sato et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Yet, on the contrary, it is noteworthy that HUT-induced gravitational stress also leads to the collapse of the internal jugular vein (IJV) by decreasing central blood volume and through mass-effect from the surrounding tissues (Dawson et al, 2004). Although it is unclear how this phenomenon contributes to CBF regulation, the venous outflow is associated with CBF regulation (Ogoh et al, 2016(Ogoh et al, , 2020Sato et al, 2017). Thus, it is possible that a gravitationally stress-induced change in venous outflow may affect CBF regulation.…”
Section: Introductionmentioning
confidence: 99%
“…Data for the D mean were obtained in three time periods, averaged, and defined as the representative value of the mean vessel diameter for each time period. On the other hand, the diameter of the cerebral veins depends on both the cardiac and respiratory cycles (Ogoh et al., 2016; Sato et al., 2017; Zamboni et al., 2016). Therefore, the systolic and diastolic venous diameters were calculated over ∼15–20 cardiac cycles guided by ECG signal to account for the oscillatory effects caused by cardiac, respiratory, or swings in intrathoracic pressure, and then the D mean was calculated as [(systolic diameter × 1/3)] + [(diastolic diameter × 2/3)].…”
Section: Methodsmentioning
confidence: 99%